Cross-Sectional Survey of Clinical Trials of Stem Cell Therapy for Heart Disease Registered at ClinicalTrials.gov - Yang, Rong; Zhang, Yonggang; Liao, Xiaoyang; Guo, Ru; Yao, Yi; Huang, Chuanying; Qi, Li (Frontiers in Cardiovascular Medicine, 2021)
Objective: It is important to register clinical trials before their implementation. There is a lack of study to evaluate registered clinical trials of stem cell therapy for heart diseases. Our study used the registration information at ClinicalTrials.gov to provide an overview of the registered trials investigating stem cell therapy for heart diseases. Methods: We searched ClinicalTrials.gov from inception to 1st October 2020 to identify clinical trials evaluating stem cell therapy for heart diseases. These trials were included in a cross-sectional survey and descriptive analysis. The outcomes included basic overview, study design and specific research content of those trials, as well as conditions, efficacy, safety and samples of the publications. Results: A total of 241 trials were included. The registration applications for most trials originated from the United States, and the research start date ranged from 2001 to 2025. More than half of the trials have been completed, but few trials have published results (15.62%). The funding source for 81.12% of trials was recorded as ‘other’. There were 226 (93.78%) interventional studies and 15 (6.22%) observational studies; among all 241 studies, only 2.90% were phase 4 trials. Of the observational studies, 6 were cohort studies (40.00%) and 73.33% were prospective. The most common disease was coronary artery disease (57.68%) and 98.34% included both male and female participants. The sample size included fewer than 50 patients in 58.51% of trials, and only 18 trials (7.47%) lasted more than 121 months. The registered details were illogical for nine trials (3.8%) that included 0 subjects and two trials (0.8%) that had a duration of 0 months (0.8%). In term of publications of the trials, most of the publications of the trials showed efficacy and safety in stem cell therapy for heart disease. Conclusion: The clinical trials investigating stem cell therapy for heart diseases registered at ClinicalTrials.gov are mostly interventional studies. Most trials have a small sample size, and few have a duration of more than 121 months. Most of the completed trials did not publish their results, and some of the registration information was incomplete and illogical.